AN ANALYSIS OF STRUGGLE OF LIFE IN “BETWEEN THE WORLD AND ME” NOVEL BY TA-NEHISI COATES - Anggun Inggrit Larasati; agus triyogo; yulfi yulfi (Journal of English Education, Literature and Linguistics, 2021)
The aim of this research was to find out the struggle of life in Between The World And Me Novel by Ta-Nehisi Coates. The data was gotten from Between The World And Me Novel published in 2015. The problem of this study was what the struggle of life found in Between The World and Me novel? The primary data source was the novel and the secondary data sources were the books and the journals. A qualitative descriptive method was used in this study to classify and analyze sentences of struggle from the novel. The data in this research was collected by some steps 1) the researcher read the sentences in Between The World And Me Novel. 2) the researcher find out the words which contain struggle of life to get the data, The result of the study show that there are seven struggle in the novel 1) struggle to fight the bad things caused by racism 2) struggle to make blacks equal to whites 3) struggle to change the notion that black people 4) struggle for legal justice in America 5) struggle to seize his right to return 6) struggle to make black people safer in America 7) struggle to get black people not to be afraid to do anything.